Bioremediasi Sludge Minyak Bumi Skala Laboratorium Menggunakan Kutur Campur Kapang Indigen Hidrokarbonoklastik Skala Laboratorium - T Agung Laksana (Seminar Nasional Lahan Suboptimal, 2021)
Agung L. 2021. Laboratory-scale petroleum sludge bioremediation using laboratory-scale hydrocarbonoclastic indigenous mold mixed culture. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 154-161. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Petroleum production exploration activities, in addition to producing crude oil, also produce waste in the form of sludge containing chemicals that are toxic to the environment. Hydrocarbonoclastic mold is a type of mold that can decompose hydrocarbon compounds contained in the sludge into smaller and environmentally friendly fractions. This study aimed to find out the ability of mixed culture of hydrocarbonoclastic indigenous molds by treatment with sludge:top soil, N:P:K ratio and type of bulking agent. The design for the treatment used a completely randomized design with a factorial pattern with three treatment factors: sludge:top soil ratio of 1:1 and 2:1, N:P:K ratio of 5:1:0,5 and 10:1:0,5, bulk agent in the form of sawdust and rice husk weighing 5% of the total sludge: top soil.  The number of treatment combinations consisted of 8 units and each unit was made 3 treatments.  The results of the study showed that the combination treatment between the sludge:top soil ratio of 1:1, the ratio of N:P:K of 10:1:0.5 and the type of bulking agent in the form of rice husks decreased most highly in the percentage of total petroleum hydrocarbon degradation, which was 74.2%.  And the interaction of three treatment factors, namely sludge: top soil, N:P:K ratio and the type of bulking agent gave an effect on the percentage reduction in total petroleum hydrocarbon. It is suggested